THE CHALLENGES OF REALIZATION IN A GLOBAL CIVILIZATION - James Winston Morris (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2011)
The contemporary historical situation suggests fascinating parallels with that period of the 13th/7th century when the massive destruction of the Mongol invasions opened the way for popular new forms of Islamic life and practice that eventually spread Islam throughout Asia. Today, as in earlier periods of dramatic upheaval, we can witness those processes of inspiration and awakening that give rise to the spiritual pathways of future centuries, through each soulâ€™s gradual discovery of its unique challenges and demands of ihsan. One way of describing this transformation, to use the Qurâ€™anic language adapted by Ibn â€˜Arabi, is in terms of the process of spiritual realization (tahqÄ«q) by which people discover their guiding inner relationship to those divine qualities or â€œNamesâ€ that eventually come to defi ne the meaning and purpose of their lives. Through our lifelong movement of service (â€˜ibada) to the â€œLordâ€ (rabb) constituted by each divine Name, the transformation of the soul follows a familiar, naturally ascending trajectory. It begins with a curiosity drawing us toward some particular dimension of the Real (al-Haqq); then a compelling striving leading to heightened discipline and awareness; and ultimately to the creative manifestation of that devotion through the appropriate means of teaching, communication, and new communities of fellowseekersâ€” the Qurâ€™anic â€œservants of the All-Mercifulâ€â€”that slowly emerge from this shared spiritual work of devotion, discovery and creative response. Here we point to some ways this process of civilizational renewal is unfolding around the world, focusing on three of the most far-reaching of those divine Names: the â€œservants of the All-Wiseâ€ (al-HakÄ«m), in their exploring and deciphering the infinite Signs of Godâ€™s Wisdom â€œon the horizonsâ€, in all of the sciences of nature and society; to those muhsinÅ«n and â€œservants of the Beautifulâ€ (al-JamÄ«l) whose creative acts of beauty help awaken that love and awe which mark the beginnings of each spiritual journey; or to those â€œservants of the Subtly-Graciousâ€ (al-LatÄ«f) whose lives are dedicated to deepening our understanding of the presence and meaning of each of the divine Signs â€œin our souls,â€ in the emerging science of spirituality. These â€œservants of the all- Mercifulâ€ and their communities are themselves the fi rst seeds of an emerging global civilization.